2014
DOI: 10.1073/pnas.1402768111
|View full text |Cite
|
Sign up to set email alerts
|

Energy landscape views for interplays among folding, binding, and allostery of calmodulin domains

Abstract: Ligand binding modulates the energy landscape of proteins, thus altering their folding and allosteric conformational dynamics. To investigate such interplay, calmodulin has been a model protein.Despite much attention, fully resolved mechanisms of calmodulin folding/binding have not been elucidated. Here, by constructing a computational model that can integrate folding, binding, and allosteric motions, we studied in-depth folding of isolated calmodulin domains coupled with binding of two calcium ions and associ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
246
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 180 publications
(254 citation statements)
references
References 49 publications
8
246
0
Order By: Relevance
“…Ca 2+ influences both the inherent flexibility and the conformation of each domain of CaM (SI Appendix, Fig. S9) (43)(44)(45)(46). In our simulations with Ca 2+ , all barrier heights (F1(O-LB), F2(O-LB), F3(O-LB), and F(LB-C)) are decreased (Fig.…”
Section: Resultsmentioning
confidence: 84%
See 1 more Smart Citation
“…Ca 2+ influences both the inherent flexibility and the conformation of each domain of CaM (SI Appendix, Fig. S9) (43)(44)(45)(46). In our simulations with Ca 2+ , all barrier heights (F1(O-LB), F2(O-LB), F3(O-LB), and F(LB-C)) are decreased (Fig.…”
Section: Resultsmentioning
confidence: 84%
“…In fact, structural analysis revealed that these hydrophobic residues are buried inside of apo-CaM. Upon Ca 2+ binding, the structure of CaM adopts a more extended dumbbell conformation with the hydrophobic interior exposed to solvent to facilitate the subsequent binding with targets (41)(42)(43). In addition, although Ca 2+ does not interact with the central linker directly, it can control the plasticity of the linker (10).…”
Section: Resultsmentioning
confidence: 99%
“…Such effect of phosphorylation on the intrinsic propensity toward certain local backbone conformations can be especially important for intrinsically disordered proteins, for which the long-range global interactions are less significant compared to those of well-structured proteins. In addition, the intrinsic propensity toward certain local backbone conformations of a certain amino acid is also an important input for some computational models of protein folding/aggregation and structure predictions [11][12][13][14][15][16][17]. For example, recent computational works showed that introducing amino acid-specific parameters to the intrinsic conformational propensity in the all-atom force field can drastically improve protein folding and structure predictions [18,19].…”
Section: Introductionmentioning
confidence: 99%
“…Biophysical Journal 109(2) 365-372 for ligand-binding proteins (24)(25)(26)(31)(32)(33)(34)(35)(36)(37). Both domains consist of a pair of EF-hand folds, each of which is capable of binding one calcium ion.…”
Section: Resultsmentioning
confidence: 99%